INTEGRASI TRELLO SEBAGAI FORUM DISKUSI DIGITAL UNTUK PENGEMBANGAN PROFESIONALISME GURU PJOK MELALUI LESSON STUDY DAN PROJECT-BASED LEARNING - Muhammad Habibie; Ramadhan Arifin; Budi Setiadi (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Digital transformation in education requires teachers to effectively utilize technology as a medium for collaboration and professional development. This community service program aims to enhance the competencies of elementary school Physical Education (PE) teachers in implementing the Lesson Study and Project-Based Learning (PjBL) approaches through the integration of Trello as a digital discussion forum. The program was conducted through several stages: socialization, training, mentoring, technology implementation, evaluation, and program sustainability, involving 36 participants from the Elementary School PE Teachers Working Group (KKG PJOK) in Banjarbaru. Trello was implemented to facilitate lesson planning, peer observation, reflection, and collaborative task management. Evaluation was carried out through pre-tests, post-tests, and observations of collaborative learning activities. The results showed a significant improvement in participants’ understanding of the Lesson Study stages and the implementation of PjBL, with more than 90% of participants able to identify the Lesson Study phases, relevant Trello features, and product-based PjBL assessments. These findings indicate that the use of Trello can enhance digital literacy, collaborative skills, and teachers’ readiness to apply innovative learning practices. The program is recommended to be continued and further developed as a sustainable professional development model for PE teachers in the digital era.